GHG action zone identification at the local level: Emissions inventory and spatial distribution as methodologies for policies and plans - Marchi, Michela; Capezzuoli, Francesco; Fantozzi, Pier Lorenzo; Maccanti, Matteo; Pulselli, Riccardo Maria; Pulselli, Federico Maria; Marchettini, Nadia (Journal of cleaner production, 2023)
Climate change mitigation and adaptation policies play a role in the political agendas of local authorities. The number of monitoring tools and experiences is progressively increasing also due to improvement in standardization of methods and proliferation of research and accounting experiments, which bring about increase in awareness of political subjects and the general public. Coherently with its Sustainable Energy Action Plan (SEAP), in 2018 the Municipality of Grosseto (central Italy) decided to build a greenhouse gas (GHG) emissions inventory integrated with Geographic Information Systems (GIS)-based maps, to visualize the spatial distribution of the GHG balance results. A bottom-up GHG emissions inventory at the sub-national level has been elaborated, following the most recent Intergovernmental Panel on Climate Change (IPCC) Guidelines, with the aim of creating site-specific knowledge and supporting policies. GHG gross emissions corresponded to 395,558.59 t carbon dioxide equivalents (CO2eq), i.e. five time higher than CO2 absorption, determining an abatement percentage of 17.09%. The emissions came mainly from road transport (47.57%), heating (15.01%), and consumption of imported electricity (14.57%). The GHG emissions balance results have been translated into five geo-referenced GIS-based maps, which help localize the areas under stress and categorize the territory into GHG action zones, able to stimulate environmental policies and monitor their efficacy. Beside policies inspired by the key categories of the GHG emissions inventory (e.g., mobility, import of electricity, heating), the spatial visualization of results stimulates considerations and measures regarding the localization of activities and infrastructures, urban and environmental planning, and land use change, which are not always supported by adequate information in the case of sub-national administrative systems. Moreover, by virtue of reliability and replicability, the obtained results (i.e., climate-altering emission maps and GHG action zones identification) should be incorporated into the so-called Baseline and Monitoring Emission Inventories, required in the Sustainable Energy and Climate Action Plan (SECAP) of the municipalities that join the Covenant of Mayors. [Display omitted] •The GHG spatial inventory of the Municipality of Grosseto (Italy) is developed.•GHG emissions and removals are spatially visualized through geo-referenced maps.•The territory is divided into GHG action zones to tailor environmental policies.•The GHG geographical mosaic provides a systemic overview of the GHG emissions.•GHG maps should be incorporated in the Sustainable Energy and Climate Action Plans.